CSE-8, a filamentous fungus-specific Shr3-like chaperone, facilitates endoplasmic reticulum exit of chitin synthase CHS-3 (class I) in Neurospora crassa - González-Téllez, Samantha Verónica; Riquelme, Meritxell (Frontiers in Fungal Biology, 2025)
Chitin is a crucial structural polysaccharide in fungal cell walls, essential for maintaining cellular plasticity and integrity. Its synthesis is orchestrated by chitin synthases (CHS), a major family of transmembrane proteins. In Saccharomyces cerevisiae, the cargo receptor Chs7, belonging to the Shr3-like chaperone family, plays a pivotal role in the exit of Chs3 from the endoplasmic reticulum (ER) and its subsequent activity in the plasma membrane (PM). However, the auxiliary machinery responsible for CHS trafficking in filamentous fungi remains poorly understood. The Neurospora crassa genome encodes two orthologues of Chs7: chitin synthase export (CSE) proteins CSE-7 (NCU05720) and CSE-8 (NCU01814), both of which are highly conserved among filamentous fungi. In contrast, yeast forms only possess a single copy CHS export receptor. Previous research highlighted the crucial role of CSE-7 in the localization of CHS-4 at sites of cell wall synthesis, including the Spitzenkörper (SPK) and septa. In this study, CSE-8 was identified as an export protein for CHS-3 (class I). In the Δcse-8 knockout strain of N. crassa, CHS-3-GFP fluorescence was absent from the SPK or septa, indicating that CSE-8 is required for the exit of CHS-3 from the ER. Additionally, sexual development was disrupted in the Δcse-8 strain, with 20% of perithecia from homozygous crosses exhibiting two ostioles. A Δcse-7;Δcse-8 double mutant strain showed reduced N-acetylglucosamine (GlcNAc) content and decreased radial growth. Furthermore, the loss of cell polarity and the changes in subcellular distribution of CSE-8-GFP and CHS-3-GFP observed in hyphae under ER stress induced by the addition of tunicamycin and dithiothreitol reinforce the hypothesis that CSE-8 functions as an ER protein. The current evidence suggests that the biogenesis of CHS exclusive to filamentous fungi may involve pathways independent of CSE-mediated receptors.